PERAN PEMBELAJARAN IPAS DAN LINGKUNGAN SEKOLAH TERHADAP SIKAP SOSIAL PESERTA DIDIK DI SEKOLAH DASAR - Tina Nurul Wahidah; Ayu Lestari; Siti Widia Sulistia; Maulia Putri; Leli Inriani; Dine Trio Ratnasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explain the contribution of Natural and Social Science (IPAS) teaching, as well as the school environment, in shaping students' social attitudes at the elementary school level. The approach used is a literature study with a qualitative method through the analysis of various journals, books, and related research findings published over the past decade. The findings of this review show that IPAS teaching contributes to the development of social attitudes through experiential learning activities, problem-solving, and group collaboration, allowing students to interact, cooperate, and appreciate differences. In addition, a conducive school environment which includes school culture, teacher role modeling, supporting facilities, and relationships among school community membersnplays an important role in fostering social values such as empathy, discipline, responsibility, and tolerance. Overall, the integration of contextual IPAS learning with a positive school environment is able to optimally strengthen the development of students' social attitudes.